한의학 임상현장에서의 철학 상담의 적용: 제언과 사례분석 - 김종우; Jong-woo Kim; 곽희용; Hui-yong Kwak; 정선용; Sun-yong Chung (동의신경정신과학회지, 2019)
Objectives: This study suggests the application of philosophical counseling in the clinical field of Korean medicine and analyze the specific case. Methods: Through the analysis of coexisting factors of Korean medicine and philosophical counseling, we establish the area of philosophical counseling that Korean medicine practitioner can apply in the medical field. We described effects of philosophical counseling on the patient’s symptom and the progress after discharge through a counseling approach based on philosophical questions. Results: During philosophical counseling, the Korean medical doctor asks questions about the nature of suffering and encourages patients to gain insight into their problems. In answering the vital philosophical questions, the patient leads to a creative interpretation of future life directions. We described the method of specific approaches through the description of the two cases. Conclusions: The philosophical counseling is compatible with the concept of Korean medicine, therefore, a Korean medicine practitioner can induce the recovery of mind and body through the creative interpretation of the patient by asking the patient the appropriate question which causes reflective thinking.